PENERAPAN LEAN SIX SIGMA DALAM PENGENDALIAN KUALITAS PRODUK: STUDI KASUS PERUSAHAAN TEKSTIL - Adrian, Kevin; Kosasih, Wilson; Salomon, Lithrone Laricha (Universitas Tarumanagara, 2024)
The increasing number of fabric defects over the past three years has caused the company's performance to decline in terms of production. The data obtained is defect data in the period December 2019 to January 2023 from internal company data, while waste data is obtained by waste assessment questionaire and waste relationship matrix. The DMAIC method is the main method in this study, starting from defining problems and measuring process capabilities based on defects, continued with WRM and WAQ for waste type analysis, and the root of the problem in defects and waste is analyzed with fishbone diagrams. The results of this study show that the most common types of defects are holes, broken threads, and broken needles, while the types of waste that occur are waiting, overprocessing, defects, and overproduction. The root of the problem is that there are no QC procedures for raw materials, machine operating procedures, and periodic inspection procedures. By providing improvement proposals and implementing improvements, it was concluded that there was a reduction in production costs of up to 4%, an increase in work efficiency of up to 2.48%, and a manufacturing lead time of up to 35.98%.